Cost analysis of a teaching hospital in Thailand: Impacts of the first wave of COVID-19. - Nopphol Witvorapong; Sureerat Ngamkiatphaisan; Jiruth Sriratanaban (PLoS ONE)
COVID-19 has had adverse impacts on the health sector in Thailand and information on hospital costs is required for planning and budgeting. The aim of this study was to estimate costs that the pandemic imposed on a teaching hospital in the country, focusing on the first wave which took place in March-May 2020. A retrospective cost analysis was performed. Data on COVID-related activities, including when and where they were undertaken, were retrieved from existing sources and supplemented by in-depth interviews with the hospital's staff. The data collection period was January-October 2020, covering three distinct phases: before, during, and after the first wave of the pandemic. The total costs during the preparation phase in January-February, the pandemic phase in March-May, and the standby phase in June-October were 0.6, 3.9, and 1.2 million US dollars respectively. Costs related to treatment of COVID-19 patients were higher than those related to infection control in the first two phases but not in the standby phase, making up 82.09%, 75.23%, and 43.95% of the total costs in the three phases respectively. Costs were incurred in all areas of the hospital, including those that were set up to serve COVID patients, those serving non-COVID patients, and those serving both groups. Public donations were integral to the provision of services and made up 20.94% of the total cost during the pandemic phase. This study was the first to estimate hospital costs of COVID-19 in Thailand. It demonstrated high costs of a national outbreak and supported the establishment of a contingency fund for medical emergencies at the hospital level.